Using venous blood gas analysis in the assessment of COPD exacerbations: a prospective cohort study - McKeever, Tricia M.; Hearson, Glenn; Housley, Gemma; Reynolds, Catherine; Kinnear, William; Harrison, Timothy W.; Kelly, Anne-Maree; Shaw, Dominick E. (Thorax, 2016)
Introduction: Identifying acute hypercapnic respiratory failure is crucial in the initial management of acute exacerbations of COPD. Guidelines recommend obtaining arterial blood samples but these are more difficult to obtain than venous. We assessed whether blood gas values derived from venous blood could replace arterial at initial assessment.